Corporate governance in Germany: Productive and financial challenges - Mary O'Sullivan (Levy Economics Institute of Bard College, 1998)
The postwar system of corporate governance in Germany is being threatened by the failure of some industries to maintain their competitive position (with resulting significant job losses) and pressures for financial liquidity driven by those who have accumulated substantial financial holdings, institutions competing for control of those holdings, and those concerned about the funding of the pension system. The strength of the competitors (mainly the Japanese) lies not in cost differences, but in their capabilities, based on financial commitment and organizational integration, to innovate and thereby to build the long-run future of the corporation. If German labor, finance, and corporate managers each insist on pursuing independent strategies to extract returns from industrial enterprises and if corporations replace investment in innovation with shareholder value as the basis for corporate decision making, German industry may be unable to regenerate the basis of sustainable prosperity.
Keywords: 330